2014
DOI: 10.1620/tjem.232.9
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Expression Is Predictive of Poor Prognosis in Pharyngolaryngeal Cancer: Systematic Review and Meta-Analysis

Abstract: Pharyngolaryngeal cancer is one of the most common head and neck cancer worldwide, and the early diagnosis and prognosis prediction are still difficult because of lacking in reliable cell markers. Although the expression of CD44 has been reported to correlate with poor prognosis of pharyngolaryngeal cancer in most literatures, some controversies still exist. Since the limited patient numbers within independent studies, here we performed a meta-analysis to clarify the correlations between CD44 expression and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“… 34 36 Moreover, CD44 is found to promote migration and proliferation in gastric cancer cells. 37 , 38 In agreement with these results, our study revealed that Twist2 positively regulated the expression of ITGA6 and CD44 at both mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 90%
“… 34 36 Moreover, CD44 is found to promote migration and proliferation in gastric cancer cells. 37 , 38 In agreement with these results, our study revealed that Twist2 positively regulated the expression of ITGA6 and CD44 at both mRNA and protein levels.…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the differences in gene and environment among the ethnicity. These results were consistent with prior reports of meta-analysis in gastric cancer, 13 pharyngolaryngeal cancer, 32 colorectal cancer, 33 hepatocellular carcinoma, 14 esophageal cancer, 15 and osteosarcoma. 16 …”
Section: Discussionsupporting
confidence: 93%
“…In many other malignancies, multiple molecular markers, such as CD44, mircroRNAs expression are being used increasingly to predict prognosis and guide treatment [26, 27]. HPV-positive head and neck cancers have better prognosis than HPV-negative ones, especially given the general trend of earlier diagnoses of the more symptomatic laryngeal cancers [28].…”
Section: Discussionmentioning
confidence: 99%